Electrical and optical properties of nanocomposite MEH-PPV: ZnO prepared at different composition/ Mohd Hidayatullah Ibrahim Abdul Rahim - Abdul Rahim, Mohd Hidayatullah Ibrahim (2010)
Research on organic based light emitting diode (OLED) has become current interest due to high potential as flat panel displays. OLED is form by a layer of organic compounds sandwiched between two electrodes. In this study, the compound that has been selected for OLED application is nanocomposite MEH-PPV:ZnO. The preparation of MEH-PPV and nanocomposite solution was done using toluene as the solvent. Nanocomposite MEH-PPV:ZnO thin films were deposited using spin-coating method. The objective of this paper is to find the optimum parameter of nanocomposite MEHPPV:ZnO thin films for OLED application by preparing the thin films using different composition ratio. The electrical and optical properties have been observe for nanocomposite MEH-PPV:ZnO thin films. The electrical characterization was investigated for the conductance behavior of the thin films. By adding more compound of ZnO to the thin films, the conductivity was improved due to the increasing of carrier concentration. For optical measurement, there are two characterizations were applied which electrical and optical characteristics. The electrical properties were analyzed using 2-probe Current-Voltage (I-V) measurement system (Advantest R6243). For optical, Ultraviolet-Visible (UV-Vis) spectrophotometer and Photoluminescence (PL) spectroscopy were used. From the electrical results, it shows the composition ratios of MEH-PPV:ZnO nanocomposite give the inversely proportional relation to the resistivity which related to the carrier concentration. The optical measurement found that the quenching of luminescence with the presence of ZnO. This is due to the attributed of reduction in the emissive materials.